COMPOSITION OF CATCH RESULTS BASED ON THE SIZE OF KURAU NETS IN MESKOM VILLAGE, BENGKALIS REGENCY RIAU PROVINCE - Heryan Hadi Kusuma; Bustari Bustari; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT Kurau net is a type of active fishing gear that drifts and traps other fish caught in the Kurau net. The construction of the Kurau net is very simple. This research was conducted in Meskom Village, Bengkalis Regency, Riau Province in February 2021. This study aims to determine the composition of the catch type and amount of target fish catch and bycatch kurau nets with different mesh sizes operated in Meskom Village, Kab. Bengkalis Riau Province. This research was conducted using survey and literature methods. The results showed that the catches caught in the Kurau Net with mesh size 4 and the Kurau net in 7 meshes yielded different catches, namely the Kurau net with mesh size 4 obtained 4 types of fish in the form of White Snapper (Lates calcalifer), Grouper Red (Plectropomus leopardus), Mackerel (Scomberomorus) and Parang fish (Chirocentrus Dorab) while the catch of kurau nets with mesh size 7 found 1 type of fish, namely Kurau fish (Eleuheronema tetradaccylum)Keywords : Catch, Mesh Size 4 and.